IPAA Is More "Desmoidogenic" Than Ileorectal Anastomosis in Familial Adenomatous Polyposis. Issue 11 (23rd November 2021) - Sommovilla, Joshua; Liska, David; Jia, Xue; Kalady, Matthew F.; Sklow, Bradford; Burke, Carol A.; Leach, Brandie H.; Steele, Scott R.; Church, James M.
Abstract : BACKGROUND: Desmoid disease is a leading cause of morbidity and mortality in patients with familial adenomatous polyposis. Abdominal desmoid disease usually follows total proctocolectomy with IPAA or total abdominal colectomy with ileorectal anastomosis. Sex, extraintestinal manifestations, and a 3′-mutation location have been identified as risk factors, but surgical risk factors are poorly understood. We hypothesized that pouch construction creates a higher risk of desmoid formation due to the increased stretch of the small-bowel mesentery. OBJECTIVE: This study aimed to investigate the surgical risk factors for desmoid formation. DESIGN: This was a retrospective, single-center, registry-based cohort study. SETTINGS: This study was conducted at a single academic institution with a prospectively maintained hereditary colorectal cancer database between 1995 and 2015. PATIENTS: All patients with familial polyposis (total 345) who underwent either proctocolectomy with a pouch or colectomy with an ileorectal anastomosis during the study period and met inclusion criteria were selected. MAIN OUTCOME MEASURES: The development of symptomatic abdominal desmoid disease was the primary end point. Associations between desmoid formation and resection type, surgical approach, and other patient factors were analyzed. RESULTS: A total of 172 (49%) patients underwent proctocolectomy/ileoanal pouch, whereas 173 (51%) underwent total colectomy/ileorectal anastomosis. Overall, 100 (28.9%) developed symptomatic desmoids after surgery. On univariable analysis, open surgery and pouch surgery were associated with desmoid development, along with extracolonic manifestations, family history of desmoids, mutation location, and a high desmoid risk score. On multivarible analysis, proctocolectomy with pouch was most strongly associated with desmoid disease ( p < 0.01). LIMITATIONS: This study was limited by its retrospective nature, the lack of uniform desmoid screening, and the variable duration of follow-up. Unanalyzed confounding factors include polyposis severity and number of surgeries. CONCLUSIONS: Patients with polyposis who underwent total proctocolectomy with pouch by any approach had significantly greater risk of developing desmoid disease than total colectomy with ileorectal anastomosis, even when accounting for other risk factors. See Video Abstract at http://links.lww.com/DCR/B822 . RESULTADOS DE LOS PACIENTES SOMETIDOS A RESECCIÓN INTESTINAL ELECTIVA ANTES Y DESPUÉS DE LA IMPLEMENTACIÓN DE UN PROGRAMA DE DETECCIÓN Y TRATAMIENTO DE ANEMIA ANTECEDENTES: Se sabe que los pacientes anémicos que se someten a una cirugía electiva de cáncer colorrectal tienen tasas significativamente más altas de complicaciones posoperatorias y peores resultados. OBJETIVO: Mejorar las tasas de detección y tratamiento de la anemia en pacientes sometidos a resecciones electivas de colon y recto a través de una iniciativa de mejora de calidad. DISEÑO: Comparamos una cohorte histórica de pacientes antes de la implementación de nuestro programa de detección de anemia y mejora de la calidad del tratamiento con una cohorte prospectiva después de la implementación. ENTORNO CLINICO: Hospital de atención terciaria. PACIENTES: Todos los pacientes adultos con un nuevo diagnóstico de cáncer de colon o recto sin evidencia de enfermedad metastásica entre 2017 y 2019. INTERVENCIONES: Detección de anemia y programa de mejora de la calidad del tratamiento. PRINCIPALES MEDIDAS DE RESULTADO: El resultado primario fue el costo hospitalario por ingreso. RESULTADOS: Un total de 84 pacientes se sometieron a resección electiva de colon o recto antes de la implementación de nuestro proyecto de mejora de calidad de la anemia y 88 pacientes se sometieron a cirugía después. En la cohorte previa a la implementación, 44/84 (55, 9 %) presentaban anemia en comparación con 47/99 (54, 7 %) en la cohorte posterior a la implementación. Las tasas de detección (25 % a 86, 4 %) y tratamiento (27, 8 % a 63, 8 %) aumentaron significativamente en la cohorte posterior a la implementación. El costo total medio por admisión se redujo significativamente en la cohorte posterior a la implementación (costo medio 16 827 vs. 25 796, p = 0, 004); esta reducción significativa se observó incluso después de ajustar los factores de confusión relevantes (proporción de medias: 0, 74, IC del 95 %: 0, 65 a 0, 85). El vínculo mecánico entre el tratamiento de la anemia y la reducción de costos sigue siendo desconocido. No hubo diferencias significativas en las tasas de transfusión de sangre, complicaciones o mortalidad entre los grupos. LIMITACIONES: El diseño de antes y después está sujeto a sesgos temporales y de selección. CONCLUSIONES: Demostramos la implementación exitosa de un programa de detección y tratamiento de anemia. Este programa se asoció con un costo por admisión significativamente reducido. Este trabajo demuestra el valor y los beneficios posibles de la implementación de un programa de detección y tratamiento de la anemia. Consulte Video Resumen en http://links.lww.com/DCR/C15 . (Traducción— Dr. Francisco M. Abarca-Rendon )